ENGLISH LANGUAGE PROFICIENCY AND THE PROFESSIONAL EMPLOYMENT OUTCOMES OF OVERSEAS ACCOUNTING STUDENTS IN AUSTRALIA: AN EMPIRICAL TEST - Christopher, Theo; Hayes, Colleen (The journal of contemporary issues in business and government, 2008)
This study compares the performance of local and overseas accounting students studying in a West Australian university with respect to a written and a practical component of an examination question associated with a second year level accounting unit. An analysis of the results, using an analysis of variance, indicated that the language background for these two groups of students was a significant discriminating variable with respect to the written, but not the practical, component. This result suggests that the standard of written English language skills of overseas students is below that of their local counterparts, and this outcome lends support to the assertion that English language difficulties contribute to overseas graduates being less likely to gain professional employment than their local counterparts. Notwithstanding the extreme importance and implications of this research for concerned stakeholders including educators, educational institutions, graduates, employers and regulators, the research findings are tentative and further research is needed in relation to both academic performance and professional employment outcomes.